Existence of solutions for second-order integral boundary value problems - Cui, Yujun; Zou, Yumei (Nonlinear Analysis: Modelling and Control, 2016)
In this paper, using a new comparison result and monotone iterative method, we consider the existence of solution of integral boundary value problem for second-order differential equation. To obtain corresponding results, we also discuss second order differential inequalities. The interesting point is that the one-sided Lipschitz constant is related to the first eigenvalues corresponding to the relevant operators.